DETECTION OF Escherichia coli AND TOTAL PLATE COUNT OF BACTERIA IN PIG LAWAR IN ABIANSEMAL DISTRICT, BADUNG REGENCY, BALI PROVINCE - Antini, Ni Ketut Febri; Kawuri, Retno; Wijana, I Made Sara (SIMBIOSIS, 2022)
ABSTRACT Lawar babi is a Balinese food that is much liked, both by the locals and by tourists visiting Bali. Good and healthy food must be free of pathogenic bacteria and must meet the maximum threshold for bacterial contamination according to the Badan Pengawas Obat dan Makanan (BPOM).  The purpose of this research was to determine the presence of Escherichia coli and the total plate count (TPC) of bacteria in lawar putih and lawar merah sold in Abiansemal District, Badung Regency, Bali Province.  Samples were taken from 10 random traders in the Abiansemal area.  This research was conducted at the Laboratory of Microbiology, Department of Biology, Faculty of Mathematics and Natural Sciences, Udayana University. Methods used in this research consists of the plating method. The test results showed that 40% of lawar merah had E. coli contamination exceeding BPOM requirements is < 3 MPN/g, while 30% of lawar putih had E. coli contamination. The highest E. coli contamination occurred in Sangeh, namely lawar merah (6.3 ± 0.76) MPN/g, while lawar putih (4.0 ± 0.49) MPN/g fluctuated. E. coli bacteria contamination in blood was highest in Sangeh at (1.9 ± 0.50) MPN/g. The results of ALT bacteria on lawar merah showed 80% did not meet BPOM requirements is < 1 x 10 6 CFU/g, while lawar putih did not meet BPOM requirements by 40%. The highest ALT value in pig blood in Sibang Gede II (Banjar Badung) was (18.97 ± 0.42) x 10 3 CFU/g. The use of fresh blood as a red dye caused an increase in bacterial contamination of lawar merah.